Sensitivity of the North Atlantic climate to Greenland Ice Sheet melting during the Last Interglacial - Bakker, P.; van Meerbeeck, C.J.V.C.; Renssen, H. (Climate of the Past, 2012)
During the Last Interglacial (LIG; ∼130 000 yr BP), part of the Greenland Ice Sheet (GIS) melted due to a warmer than present-day climate. However, the impact of this melting on the LIG climate in the North Atlantic region is relatively unknown. Using the LOVECLIM Earth system model of intermediate complexity, we have systematically tested the sensitivity of the LIG climate to increased freshwater runoff from the GIS. In addition, experiments have been performed to investigate the impact of an idealized reduction of both surface elevation and extent of the GIS on the LIG climate. Based on changes in the maximum sea-ice cover and the strength of the overturning circulation, three regimes have been identified, which are characterized by a specific pattern of surface temperature change in the North Atlantic region. By comparing the simulated deep ocean circulation with proxy-based reconstructions, the most realistic simulated climate could be discerned. The resulting climate is characterized by a shutdown of deep convection and a subsequent ~4 °C cooling in the Labrador Sea. Furthermore, a cooling of ~1 °C over the North Atlantic Ocean between 40° N and 70° N is seen. The prescribed reduction in surface elevation and extent of the GIS results in a local warming of up to 4 °C and amplifies the freshwater-forced reduction in deep convection and the resultant cooling in the Nordic Seas. A further comparison of simulated summer temperatures with both continental and oceanic proxy records reveals that the partial melting of the GIS during the LIG could have delayed maximum summer temperatures in the western part of the North Atlantic region relative to the insolation maximum. © Author(s) 2012.